2000
DOI: 10.2527/2000.781139x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acids, prostaglandin F2alpha metabolite, and reproductive response in postpartum heifers fed rumen bypass fat.

Abstract: An experiment was conducted to determine whether feeding rumen-protected fatty acids (FA) to postpartum heifers would increase plasma concentrations of linoleic acid and PGF2, metabolite (PGFM), shorten the interval from calving to first increase in plasma concentrations of progesterone (P4), and increase pregnancy rate relative to controls. Hereford x Angus heifers (346 kg) were assigned randomly to treatments containing either lipid or barley supplemented diets for the first 30 d postpartum. Lipid was .23 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
3
20
0
1
Order By: Relevance
“…The similarity in daily DMI across diets was mirrored in animal performance with no effect on ADG, consistent with the report of Wistuba et al (2006). Despite evidence of a diet 3 day interaction for plasma concentrations of some FA measured, concentrations of most FA were generally consistent with other published reports (Filley et al, 2000;Burns et al, 2003) involving similar dietary approaches. Consequently, rather than discussing the effect of diet on each FA measured, we focus on a select number of FAs in the context of their potential biological roles in metabolism and reproduction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The similarity in daily DMI across diets was mirrored in animal performance with no effect on ADG, consistent with the report of Wistuba et al (2006). Despite evidence of a diet 3 day interaction for plasma concentrations of some FA measured, concentrations of most FA were generally consistent with other published reports (Filley et al, 2000;Burns et al, 2003) involving similar dietary approaches. Consequently, rather than discussing the effect of diet on each FA measured, we focus on a select number of FAs in the context of their potential biological roles in metabolism and reproduction.…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, rather than discussing the effect of diet on each FA measured, we focus on a select number of FAs in the context of their potential biological roles in metabolism and reproduction. The addition of the whole soya beans increased the concentrations of linoleic acid in plasma consistent with other studies involving dietary supplementation of cattle with a source of linoleic acid (Filley et al, 2000;Burns et al, 2003). The linoleic acid content of cattle follicular fluid and of oocytes is apparently important for oocyte developmental competence (Homa and Brown, 1992) and has been shown to be important for blastulation in in vitro fertilisation studies (Zeron et al, 2001).…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, Brahman cows supplemented with 530 g·d -1 lipid from rice bran containing approximately equal proportions of oleic and linoleic acid tended to have increased concentrations of serum PGFM [4]. Likewise, beef cows fed 230 g·d -1 calcium soaps of fatty acids containing 40% oleic and 9% linoleic acid also had increased concentrations of PGFM early in the postpartum period [5].…”
Section: Discussionmentioning
confidence: 91%
“…High serum concentrations of PGFM early postpartum decreases the time required for uterine involution [20]. Filley et al [5] reported a negative correlation between the duration of increased PGF 2α production and the duration of the postpartum anestrous period. Conversely, high serum concentrations of PGF 2α later in the postpartum interval may reduce subsequent fertility by increasing the incidence of estrous cycles with abbreviated luteal phases resulting in early embryonic mortality [10,21,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation